Attractiveness Compensates for Low Status Background in the Prediction of Educational Attainment - Bauldry, Shawn; Shanahan, Michael J.; Russo, Rosemary; Roberts, Brent W.; Damian, Rodica (PLOS ONE, 2016)
Background People who are perceived as good looking or as having a pleasant personality enjoy many advantages, including higher educational attainment. This study examines (1) whether associations between physical/personality attractiveness and educational attainment vary by parental socioeconomic resources and (2) whether parental socioeconomic resources predict these forms of attractiveness. Based on the theory of resource substitution with structural amplification, we hypothesized that both types of attractiveness would have a stronger association with educational attainment for people from disadvantaged backgrounds (resource substitution), but also that people from disadvantaged backgrounds would be less likely to be perceived as attractive (amplification). Methods This study draws on data from the National Longitudinal Study of Adolescent to Adult Health—including repeated interviewer ratings of respondents’ attractiveness—and trait-state structural equation models to examine the moderation (substitution) and mediation (amplification) of physical and personality attractiveness in the link between parental socioeconomic resources and educational attainment. Results Both perceived personality and physical attractiveness have stronger associations with educational attainment for people from families with lower levels of parental education (substitution). Further, parental education and income are associated with both dimensions of perceived attractiveness, and personality attractiveness is positively associated with educational attainment (amplification). Results do not differ by sex and race/ethnicity. Further, associations between perceived attractiveness and educational attainment remain after accounting for unmeasured family-level confounders using a sibling fixed-effects model. Conclusions Perceived attractiveness, particularly personality attractiveness, is a more important psychosocial resource for educational attainment for people from disadvantaged backgrounds than for people from advantaged backgrounds. People from disadvantaged backgrounds, however, are less likely to be perceived as attractive than people from advantaged backgrounds.